The Anti-inflammatory Effect of the Tricyclic Antidepressant Clomipramine and Its High Penetration in the Brain Might Be Useful to Prevent the Psychiatric Consequences of SARS-CoV-2 Infection - Nobile, B.; Durand, M.; Olié, E.; Guillaume, S.; Molès, J. P.; Haffen, E.; Courtet, P. (Frontiers in Pharmacology, 2021)
At the time of writing (December 2020), coronavirus disease 2019 (COVID-19) has already caused more than one million deaths worldwide, and therefore, it is imperative to find effective treatments. The “cytokine storm” induced by Severe Acute Respiratory Syndrome-Coronavirus type 2 (SARS-CoV-2) is a good target to prevent disease worsening, as indicated by the results obtained with tocilizumab and dexamethasone. SARS-CoV-2 can also invade the brain and cause neuro-inflammation with dramatic neurological manifestations, such as viral encephalitis. This could lead to potentially incapacitating long-term consequences, such as the development of psychiatric disorders, as previously observed with SARS-CoV. Several pathways/mechanisms could explain the link between viral infection and development of psychiatric diseases, especially neuro-inflammation induced by SARS-CoV-2. Therefore, it is important to find molecules with anti-inflammatory properties that penetrate easily into the brain. For instance, some antidepressants have anti-inflammatory action and pass easily through the blood brain barrier. Among them, clomipramine has shown very strong anti-inflammatory properties in in vitro, in vivo (animal models) and human studies, especially in the brain. The aim of this review is to discuss the potential application of clomipramine to prevent post-infectious mental complications. Repositioning and testing antidepressants for COVID-19 management could help to reduce peripheral and especially central inflammation and to prevent the acute and particularly the long-term consequences of SARS-CoV-2 infection.